Cross-layer reliability of computing systems - Di Natale, Giorgio; Gizopoulos, Dimitris; Di Carlo, Stefano; Bosio, Alberto; Canal, Ramon (The Institution of Engineering and Technology, 2020)
This book presents state-of-the-art solutions for increasing the resilience of computing systems, both at single levels of abstraction and multi-layers. It is a valuable resource for researchers, postgraduate students and professional computer architects focusing on the dependability of computing systems
Keywords: Computer architecture.; Stochastic processes.; elektronické knihy; electronic books